Applying High-Frequency Oscillatory Ventilation (HFOV) Successfully in Idiopathic Pulmonary Fibrosis Patient, Potential Challenge - Ahmad Alessa, Reem Ghazzawi, Tahani Alghamdi, Bashayer Altowerqy, Bashaer Al Sarhan, Ali Alanazi, Noha Alhothaly, Ghufran Ghouthali, (Pakistan Journal of Medical & Health Sciences, 2022)
Patients with Idiopathic pulmonary fibrosis (IPF) are known to frequently experience the life-threatening consequence of pneumothorax. Pneumothorax is a buildup of air around the lung but inside the pleural cavity. It happens when air gathers inside the chest between the visceral and parietal pleura. This idiopathic pulmonary fibrosis and pneumothorax lead to surgical emphysema. It occurs when gas or air seeps into the subcutaneous tissue (the skin's lowest layer). The main objective of this clinical case study is to determine how the patient’s requirements and ABG change when one condition leads to another. A patient of 60 years with a medical history came to the emergency department with a chief complaint of shortness of breath and chest pain. On his arrival, the oxygen saturation was 68% at room air, and a chest X-ray revealed pneumothorax. He was then shifted to a pulmonary team to floor as surgical emphysema, secondary pneumothorax (right) on intercostal space chest tube, and CAP (community-acquired pneumonia). ABG tests were taken after every step of the lung-protective strategy: post-intubation, post-HFOV connection, after disconnection, after switching to PCMV, and post-HFOV disconnection. These results indicate the severity of the patient’s condition. Even after the percutaneous tracheostomy procedure, the patient was still experiencing the challenges of increased oxygen requirements and recurrent spontaneous pneumothorax. Keywords: Idiopathic pulmonary fibrosis (IPF), Pneumothorax, High frequency oscillatory ventilation (HFOV), acute respiratory distress syndrome (ARDS)